Patient-derived organoids and mini-PDX for predicting METN375S-mutated lung cancer patient clinical therapeutic response - Meng Jiang; Rongfu Tu; Yiwen Pan; Yuxin Cui; Xin Qi; Hongyu Qin; Lijuan Liu; Xiaorui Wang; Ying Xue; Yao Xu; Ziyang Peng; Chengsheng Zhang; et al. (Heliyon, 2024)
Lung cancer as a molecularly and histologically high heterogonous disease, there is an urgent need to predict lung cancer patients' responses to anti-cancer treatment, and patient-derived organoids (PDOs) have been recognized as a valuable platform for preclinical drug screening. In this study, we successfully established 26 PDO lines from various subtypes of lung cancers including benign tumor, adenocarcinoma, squamous cell carcinoma, adenosquamous carcinoma, large-cell carcinoma, and small-cell carcinoma. These PDOs were shown to retain the major genomic and histological characteristics of primary tumors and remain stable during long-term culture. With the help of targeted genomic sequencing, we found that lung cancer that harbors METN375S mutation is selectively sensitive to afatinib, and a combination of afatinib and gemcitabine induced synthetic lethality in PDO and mini-PDX models. In summary, our findings demonstrate the potential of PDO in predicting lung cancer drug response, and reveal a promising strategy for METN375S mutant lung cancer treatment.